Association between Obesity and Symptoms of Depression of Adults in Puerto Rico - Laborde, José E.; Sáez-Santiago, Emily (Puerto Rico Health Sciences Journal, 2013)
Objective: This study was aimed at determining the prevalence of overweight; of class 1 and class 2/3 obesity; and of the symptoms of depression in adults in Puerto Rico. The study also evaluated the relationship between the symptoms of depression and weight status. Methods: The sample for this study consists of 6,025 adults (3,851 females and 2,174 males) who lived in Puerto Rico at the time of and who participated in either the 2006 or the 2010 BRFSS. Results: In this sample 70.0% of the respondents were either overweight or obese. About 39.6% of them were considered overweight, while 18.1% were obese class 1 and 12.3% were obese class 2 or 3. When compared by gender, the prevalence rate of overweight was higher for males (46.9%) than it was for females (35.5%), but females (14.1%) had a higher rate of class 2/3 obesity than did males (9.2%). There were no significant gender-based differences in the class 1 (BMI between 30 and 35) obesity group. According to the study’s findings, depression symptoms and class 1 obesity are not strongly associated. A positive relationship between depression and weight was found only in women with class 2/3 obesity (BMI>35). Conclusion: In summary, the results of this study show that depressive symptoms are associated with obesity, and this correlation seems to be more significant in women, especially those with severe obesity, less education, and lower incomes. Findings point to the existence of a high risk of comorbid obesity and depression of adults in Puerto Rico.